2016
DOI: 10.1136/injuryprev-2015-041911
|View full text |Cite
|
Sign up to set email alerts
|

Blood alcohol and injury in Bhutan: targeted surveillance in a national referral hospital emergency department

Abstract: Bhutan is a low-middle-income country with poor roads, rapidly increasing motor vehicle use and heavy alcohol consumption. We estimated the proportion of emergency department patients presenting with injury who had positive blood alcohol. We sought to breathalyse and interview all adult patients (≥18 years) presenting with injury at the Jigme Dorji Wangchuck National Referral Hospital in the capital city Thimphu, from April to October 2015. Breath tests and interviews were conducted with 339 (91%) of 374 eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…There were 100 records that reported on the prevalence of AOD involvement in injury events. Of the 100 records that reported on all causes of injury (excluding transport events), 30 studies reported on the prevalence of AOD involvement in patients presenting to hospital after falls 24–52. One of these studies was excluded, since it reported exclusively on patients who denied consuming alcohol in the past year 38.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 100 records that reported on the prevalence of AOD involvement in injury events. Of the 100 records that reported on all causes of injury (excluding transport events), 30 studies reported on the prevalence of AOD involvement in patients presenting to hospital after falls 24–52. One of these studies was excluded, since it reported exclusively on patients who denied consuming alcohol in the past year 38.…”
Section: Resultsmentioning
confidence: 99%
“…Studies were predominantly from the USA (13 studies) 24 26–28 31 36 39 41–44 48–52. There were two studies from Norway,25 29 30 46 and one each from Bhutan,35 Ghana,37 Spain,33 34 Taiwan,32 45 Tanzania45 and the UK 40. One additional record compiled data from 22 studies across 10 countries from North and South America including Canada, the USA, Mexico, Brazil, Argentina, the Dominican Republic, Guatemala, Guyana, Nicaragua and Panama 53.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, there were 944 alcohol outlets in Thimphu, accounting for up to 17.5% of alcohol outlets in all injury victims were alcohol-positive. [54] Alcoholic liver disease continues to be in the top five causes of morbidity and mortality in Bhutan. [34,35,55] This has led to significant medical and health costs in terms of care and rehabilitation for those with alcohol dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Motivated by concern about this combination of increasing motorisation and very heavy drinking on population health, we undertook a study of alcohol‐related injury in 2015 [7]. Over a 6‐month period, we breath‐tested patients presenting with injury to the emergency department in the capital city Thimphu, finding that 34% were alcohol‐positive [blood alcohol concentration (BAC) >0] and 22% had BACs >0.08 g/dL.…”
Section: Introductionmentioning
confidence: 99%